Pelatihan Aplikasi Pembelajaran Online Berbasis Moodle Dalam Peningkatan Mutu Pembelajaran di Perguruan Tinggi - Saeful Anam (Community: Jurnal Pengabdian Kepada Masyarakat, 2021)
conducting the online learning process now needs to be controlled by every educator, this is done so that the quality of Indonesian education can always develop and advance. This service was carried out in order to provide assistance to educators in understanding and improving the quality of learning carried out by educators through the Moodle (mobile learning) application in the era of the Covid-19 pandemic. The results of this service show that 75% of the participants are satisfied and very happy with this training, and they hope for the same training next time.